Exposing Obstetric Violence in the Eastern Mediterranean Region: A Review of Women's Narratives of Disrespect and Abuse in Childbirth - Khalil, Merette; Carasso, Kashi Barbara; Kabakian-Khasholian, Tamar (Frontiers in Global Women's Health, 2022)
Background Obstetric violence (OV) threatens the provision of dignified, rights-based, high-quality, and respectful maternal care (RMC). The dearth of evidence on OV in the Eastern Mediterranean Region poses a knowledge gap requiring research to improve rights-based and respectful health practice and policy. While efforts to improve the quality of maternal health have long-existed, women's experiences of childbirth and perceptions of dignity and respect are not adequately or systematically recorded, especially in the said region. Aim This study centered on the experiences of women's mistreatment in childbirth to provide an overview of OV and offer recommendations to improve RMC. Methods A scoping review was conducted, and a total of 38 articles met the inclusion criteria and were analyzed using Bowser and Hill's framework of the seven typologies of Disrespect and Abuse (D&A) in childbirth. D&A in childbirth (or violations to RMC) is a manifestation of OV and served as a proxy to analyze its prevalence in the EMR. Findings and Discussion This study indicated that across the EMR, women experienced every type of D&A in childbirth. This happens regardless of health systems' strength or country's income, with 6 out of 7 types of D&A found in almost two-thirds of included countries. In the EMR, the most common types of D&A in childbirth are physical abuse (especially overused routine interventions) and non-dignified care (embedded in patriarchal socio-cultural norms). The intersections of these abuses enable the objectification of women's bodies and overuse of unconsented routine interventions in a hierarchical and patriarchal system that regards the power and autonomy of doctors above birthing women. If unchecked, the implications include acceptance, continuation, and underreporting of D&A in childbirth, as well as passivity toward human-rights violations, which all further cause the continuing the cycle of OV. Conclusion In order to eliminate OV, a paradigm shift is required involving infrastructure changes, education, empowerment, advocacy, a women-centered and gender-sensitive approach to health system strengthening, and policy development. Recommendations are given at individual, community, health systems, and policy levels to ensure that every woman achieves her right to health and birth in a dignified, respectful, and empowered manner.